1991
DOI: 10.1007/bf00928410
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of gold-labeled proteins and LDL byTrypanosoma cruzi

Abstract: Endocytosis was studied at the ultrastructural level in different developmental forms of Trypanosoma cruzi after incubation of the parasites in the presence of gold-labeled proteins (albumin-Au, peroxidase-Au and transferrin-Au) and low-density lipoprotein (LDL-Au). Epimastigote (culture) forms actively ingested LDL and proteins. Initially, gold particles were seen adhering only to the cytostome and inside the flagellar pocket. In parasites incubated at 4 degrees C with transferrin-Au or peroxidase-Au, labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 32 publications
3
130
0
Order By: Relevance
“…However, the physiological relevance of this interaction is unclear since amastigotes replicate in the cytoplasm of host cells, a niche in which transferrin is conspicuously absent. Consistent with this, very little intracellular staining has been detected in amastigotes using gold-labelled transferrin (Soares and de Souza, 1991). This does not exclude the possibility that trypomastigotes could pick up transferrin in the bloodstream, or that epimastigotes can acquire iron from transferrin in the bloodmeal.…”
Section: Iron Transport In Trypanosomatidsmentioning
confidence: 88%
“…However, the physiological relevance of this interaction is unclear since amastigotes replicate in the cytoplasm of host cells, a niche in which transferrin is conspicuously absent. Consistent with this, very little intracellular staining has been detected in amastigotes using gold-labelled transferrin (Soares and de Souza, 1991). This does not exclude the possibility that trypomastigotes could pick up transferrin in the bloodstream, or that epimastigotes can acquire iron from transferrin in the bloodmeal.…”
Section: Iron Transport In Trypanosomatidsmentioning
confidence: 88%
“…The presence of a P-type H + -ATPase offers additional evidence of the acidic nature of the cytostome (Vieira et al 2005). Following binding to the cytostome and flagellar pocket, macromolecules are rapidly internalized and appear in small endocytic vesicles that bud from the deeper regions of this structure (Soares & De Souza 1991). Vesicles with a clathrin-like coat were first reported to bud from the Golgi complex.…”
Section: The Endocytic Pathwaymentioning
confidence: 99%
“…It is well known that incubation of the para-sites at 28°C with gold labeled proteins results in labeling inside cytoplasmic vesicles and tubules, as well as in the reservosomes (Soares & De Souza 1991, Soares et al 1992). Figueiredo and Soares (1996) showed that incubation of the parasites at 12°C (a condition that hinders the fusion of endocytic vesicles with early endosomes in mammalian cells) blocked the pinching of endocytic vesicles at the cytostome, inhibiting the uptake of nutrients by the cells.…”
Section: The Endocytic Pathwaymentioning
confidence: 99%
“…However, epimastigotes of T. cruzi present an additional site for the uptake of macromolecules: the cytostome, a deep invagination of the cell plasma membrane close to the flagellar pocket region. It appears that the cytostome is physically linked to the flagellum (Okuda et al 1977) and represents the main site for both receptor-mediated-endocytosis and fluidphase-pinocytosis in epimastigotes (Soares & De Souza 1991. Endocytic vesicles bud off from the cytostome and the flagellar pocket membranes and then deliver their cargo to the reservosomes (Soares & De Souza 1991, Soares et al 1992.…”
Section: The Endocytic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation